First Observations From the TREx Spectrograph: The Optical Spectrum of STEVE and the Picket Fence Phenomena. Issue 13 (9th July 2019) - Gillies, D. M.; Donovan, E.; Hampton, D.; Liang, J.; Connors, M.; Nishimura, Y.; Gallardo‐Lacourt, B.; Spanswick, E.
Abstract: We present the first observations of ionospheric phenomena using the newly deployed Transition Region Explorer (TREx) Spectrograph. On the night of 10 April 2018, STEVE (Strong Thermal Emission Velocity Enhancement) and the Picket Fence optical structures were observed by the spectrograph in Lucky Lake, Saskatchewan. STEVE contains an enhancement of the OI red‐line (630‐nm) emission and a continuum which spans the visible wavelengths. Based upon its spectrum, we assert that the characteristic mauve color of STEVE is a result of this continuum. The spectrum of the Picket Fence contains a strong OI green‐line (557.7‐nm) emission similar to that produced in typical auroral structures. From their spectra, we assert that the Picket Fence is caused by particle precipitation and thus that the Picket Fence is a form of aurora, while STEVE's spectrum confirms that it is not aurora. Key Points: The Picket Fence spectrum is similar to aurora The STEVE spectrum contains a continuum similar to NO airglow STEVE is unlikely to be aurora